Manejo y tratamiento del dolor en adultos mayores con enfermedades crónicas degenerativas - Ordóñez Gallardo, Paula Nicole (2023)
Abstrac Pain is a common clinical manifestation in older adults; Its causes and origins are multiple; The identification of its semiological characteristics and the appropriate therapeutic orientation favor the reduction of the risk of functional disability and impairment of the perception of health-related quality of life. The objective of this research was to conduct a literature review to obtain updated information on the management and treatment of pain in older adults with chronic degenerative diseases. To meet the proposed objective, a basic, descriptive, documentary and transversal research was carried out, consisting of a non-systematic bibliographic review of documents published in the last 5 years related to the research topic. As a universe, 79 documents were identified, and of them 36 were part of the study sample. The information was collected from articles published in regional databases (Latindex, Lilacs, Scielo and Redalyc) and high impact databases (Scopus, Medline, PubMed and Ice Web of Sciencie). The main results include the description of the clinical and epidemiological characteristics of degenerative diseases and the pathophysiological mechanisms by which pain occurs; It was possible to define the pharmacological groups that can be used for the treatment of pain in these patients; taking into account the pathophysiological mechanisms of the degenerative process and the pharmacodynamic elements of the therapeutic groups used. It is concluded that there are therapeutic resources for the treatment of pain, their prescription should be guided by the pharmacological characteristics and the etiopathogenic mechanism of the present disease. Keywords: Older adult; Analgesia; Analgesics; Anti-inflammatories; mechanical pain; Degenerative illness; Inflammation; Osteoarthritis